1995
DOI: 10.3327/jnst.32.301
|View full text |Cite
|
Sign up to set email alerts
|

Critical Power Evaluation with Consideration of Differences in Droplet Behavior due to Spacer Shape Influence.

Abstract: A n evaluation method for droplet deposition coefficients, corresponding to spacer shapes. was developed in order to predict nuclear fuel bundle critical power. The method is based on a three-dimensional numerical analysis of dispersed flow around the spacer. The analysis showed that coolant droplet deposition characteristics onto fuel rods differed between grid type and ferrule type spacers, and also between fuel rods due to flow tabs on the upper end of the spacer band. The droplet deposition coefficient was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
4
1
Order By: Relevance
“…15(b) means the transport rate of liquid droplets to the liquid film on the rod surface. Kanazawa et al's analysis with inviscid fluid assumption showed the peak of the deposition rate in the spacer region, 8) whereas the present analysis in which the fluid is treated as the viscid fluid showed the peak downstream from the spacer. These droplet deposition characteristics obtained from the present analysis correspond to the experimental result conducted by Nishida et al…”
Section: Spacer Effectcontrasting
confidence: 44%
See 3 more Smart Citations
“…15(b) means the transport rate of liquid droplets to the liquid film on the rod surface. Kanazawa et al's analysis with inviscid fluid assumption showed the peak of the deposition rate in the spacer region, 8) whereas the present analysis in which the fluid is treated as the viscid fluid showed the peak downstream from the spacer. These droplet deposition characteristics obtained from the present analysis correspond to the experimental result conducted by Nishida et al…”
Section: Spacer Effectcontrasting
confidence: 44%
“…The basic concept in the present code to analyze the spacer effect is the same as that in the HIJET-AFIMA code. 8) However, the steam in an annular-dispersed flow region is assumed to be inviscid in the HIJET-AFIMA code, whereas it is treated as a viscid fluid in the present code. Parallel computation is applied only to the calculation of the spacer effect, since the other analytical steps do not require parallel computation because of very short computation time even with a single processor.…”
Section: Code Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, subchannel analysis is unable to predict the critical power considering the change in spacer geometry. Yamamoto et al [3] and Kanazawa et al [4] estimated a deposition enhancement coefficient due to the spacer by analyzing the behavior of droplets around the spacer using steam flow analysis. They applied the estimated coefficient to subchannel analysis and were relatively successful.…”
Section: Introductionmentioning
confidence: 99%